2018
DOI: 10.1080/20442041.2018.1494973
|View full text |Cite
|
Sign up to set email alerts
|

The European Water Framework Directive facing current challenges: recommendations for a more efficient biological assessment of inland surface waters

Abstract: High quality water is vital for human life, and ensuring its availability is a basic requirement and a major societal aim. The Water Framework Directive (WFD; 2000/60/EC) is a key piece of legislation for the protection and sustainable use of water in the European Union. In this work we briefly review the WFD directive and the current status of European inland surface waters. Additionally, we summarize major challenges and threats for the biological assessment of inland surface waters under climate change effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 62 publications
0
10
0
2
Order By: Relevance
“…This comprehensive collation was then examined to retain only methods, which fulfilled the following five criteria: (1) technology readiness level of seven or higher (European Commission, 2014), (2) comprehensive and standalone techniques (excluding sensors or analysers depending on a deployment system), (3) filling a gap in the current monitoring, (4) "novel" and not in general use, and (5) evaluated as costefficient in terms of their cost-benefit-ratio. For this compilation we considered scientific research projects [all BONUS projects since 2010 and the finished and ongoing projects listed in the Technical guidance on monitoring for the MSFD (JRC, 2014)], scientific publications (JRC, 2013;Danovaro et al, 2016;Filipe et al, 2019;Lehikoinen et al, 2019), and stakeholder suggestions. Stakeholders working in the field of environmental management and research in the Baltic countries were asked for shortcomings in the Baltic monitoring to assess the good status of the region regarding the directives MSFD, WFD and BSAP, and for novel methods with the potential to fill these.…”
Section: Identification Of Novel Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprehensive collation was then examined to retain only methods, which fulfilled the following five criteria: (1) technology readiness level of seven or higher (European Commission, 2014), (2) comprehensive and standalone techniques (excluding sensors or analysers depending on a deployment system), (3) filling a gap in the current monitoring, (4) "novel" and not in general use, and (5) evaluated as costefficient in terms of their cost-benefit-ratio. For this compilation we considered scientific research projects [all BONUS projects since 2010 and the finished and ongoing projects listed in the Technical guidance on monitoring for the MSFD (JRC, 2014)], scientific publications (JRC, 2013;Danovaro et al, 2016;Filipe et al, 2019;Lehikoinen et al, 2019), and stakeholder suggestions. Stakeholders working in the field of environmental management and research in the Baltic countries were asked for shortcomings in the Baltic monitoring to assess the good status of the region regarding the directives MSFD, WFD and BSAP, and for novel methods with the potential to fill these.…”
Section: Identification Of Novel Methodsmentioning
confidence: 99%
“…However, some studies have demonstrated relationships between the number of reads and species abundance when calculating DNA-based indices (Aylagas et al, 2018;Ushio et al, 2018;Schenk et al, 2019). In general, molecular methods have the potential to enhance the monitoring of several MSFD descriptors and thus are a promising approach for future marine monitoring (Danovaro et al, 2016;Valentini et al, 2016;Weigand et al, 2019;Filipe et al, 2019).…”
Section: Applicability Of Novel Monitoring Methodsmentioning
confidence: 99%
“…For example, large-scale nation-wide monitoring has been established in the USA and Canada through the EPA National Aquatic Resource Surveys (NARS) and the Canadian Aquatic Biomonitoring Network, respectively [1]. In Europe, homologous regulations include the Water Framework Directive (WFD, Directive 2000/60/EC) and the Marine Strategy Framework Directive (MSFD, Directive 2008/56/EC), which have been addressing aquatic environmental degradation for more than 10 years and have implemented a European-wide ecological assessment of water bodies [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…), καθώς ταυτόχρονα αναπτύχθηκαν βελτιωμένες μέθοδοι για τον έλεγχο και την αξιολόγηση της οικολογικής κατάστασης των υδατικών σωμάτων και συνεπώς αναπτύχθηκε μια καλύτερη και ευρύτερη βάση μέτρων αποκατάστασης (Voulvoulis et al, 2017). Σημειώνεται ωστόσο πως σε κράτη όπως η Ισπανία, η Πορτογαλία και η Ελλάδα, η αποτυχία επίτευξης του στόχου της τουλάχιστον καλής κατάστασης αγγίζει το 70-90% (ΕΕΑ, 2018;Filipe et al, 2019) Για τη διαχείριση των υδάτων στην Ελλάδα συντάσσονται τα Σχέδια Διαχείρισης Λεκανών Απορροής Ποταμών (ΣΔΛΑΠ) σύμφωνα με τις επιταγές της Οδηγίας Πλαίσιο για τα νερά 2000/60/ΕΚ με ευθύνη των αρμόδιων αρχών, οι οποίες αντιστοιχούν στον όρο Υδατικό Διαμέρισμα (ΥΔ) του άρθρου 3 του Π.Δ. 51/2007 (ΦΕΚ 54Α/8.3.2007).…”
Section: 6unclassified
“…για την εξαγωγή της τελικής αξιολόγησης της κατάστασης (π.χ., Borja et al, 2009), καθώς και εκτιμήσεις χαρτογράφησης σφαλμάτων τύπου Ι και τύπου ΙΙ όπως επισημαίνεται από τους Hering et al (2010). Μια ακόμα ρητορική επ' αυτού των Filipe et al (2019) είναι η ταξινόμηση και αξιολόγηση με βάση την πρόοδο της οικολογικής κατάστασης των υδατικών σωμάτων στην πάροδο του χρόνου και όχι με απόλυτα μέτρα. Αυτή είναι μια στάση με την οποία συντασσόμαστε καθώς ταιριάζει καλύτερα στο στόχο και στο όραμα της Οδηγίας περί μη επιδείνωσης της κατάστασης.…”
Section: αποτελέσματαunclassified